Demokrasi Ekonomi Dalam Hukum Ekonomi Syari’ah - Syaugi Mubarak Seff (Jurnal Risalah Hukum, 2010)
The aim of national development is in order to achieve the level of prosperity, therefore the economic system that is used, of course, the economic system that can guide and support the realization of development objectives in question. One is an Syari’ah economic system that starts from Islamic study, but the law norms arranging it sources from Islamic study relating to muamalat, where according to its principles, the rules are open, and they are different from Islamic study in a matter of praying which rules are closed, it can accommodate the new norms as far as it is not against the Syari’ah principles.